Accuracy and Reliability of Length Measurements on Three-Dimensional Computed Tomography Using Open-Source OsiriX Software. - Kim, Gihyeon; Jung, Ho-Joong; Lee, Han-Jun; Lee, Jae-Sung; Koo, Seungbum; Chang, Seung-Hwan (Journal of Digital Imaging, 2012)
There is a growing interest in three-dimensional computed tomography (3D-CT) as a research tool for the study of bone, joint anatomy, and kinematics. However, when CT data are processed and handled manually using image processing programs to yield 3D image and coordinate value, systematic and random errors should be validated. We evaluated the accuracy and reliability of length measurement on CT with OsiriX software. 3D-CT scans were made of 14 frozen pig knees with five transosseous holes in the metaphyseal portion of femur. The lengths between tunnel orifices were measured using Mitutoyo Digimatic digital calipers to establish the gold standard, and with the OsiriX program in 3D multi-planar reformatting mode for comparison. All measurements were recorded by a principal (replicate 1, trial 1) and a secondary observer (replicate 2, trial 1) and were repeated once by each observer (trial 2). The mean differences between OsiriX and real measurements were less than 0.1 mm in both replicates, and maximum differences were less than 0.3 mm. There were no significant differences between the replicates and real measurements ( p = 0.544 and 0.622 for replicates 1 and 2, respectively). The intraclass correlation coefficients (ICC) were very high between trials and between replicates (ICC = 0.998 and 0.999, respectively). For kinematic analysis of the knees, length measurements on 3D-CT using OsiriX program can be used as alternatives to real measurements with less than 0.3-mm accuracy and very high reliability.